COORDINATOR MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATION IN INTERNATIONAL STANDARD MADRASAH (MBI) AMANATUL UMMAH PACET MOJOKERTO - M. Lutfi Hanif (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The quality of education is a good or bad characteristic of the quality of education. Quality education certainly needs good and quality management from a leader who can lead an educational institution and is generally supported by complete and ideal facilities. Furthermore, this study aims to find out how the management of the madrasa coordinator improves the quality of education what factors hinder the improvement of the quality of education at MBI Amanatul Ummah, and then what strategies are used by the madrasa coordinator to overcome these inhibiting factors. In this study, the authors used a qualitative research method, which is research that produces descriptive data in the form of written or spoken words from people and behavior that can be observed using a case study approach, namely by exploring in depth how the management of madrasa heads improves the quality of education. With this research method, the researchers found that the management of madrasa coordinators in improving the quality of education at MBI Amanatul Ummah was in the form of implementing totality-based management while still paying attention to and carrying out management functions, while the constraints faced were internal and external. Then the strategy used by the madrasa coordinator in overcoming these obstacles is to make maximum effort and totality, as well as various innovations and creativity, and empower existing resources to the maximum extent possible